Nonclinical assessment of abuse potential for new pharmaceuticals - Markgraf, Carrie G.; Hudzik, Thomas J.; Compton, David R. (Academic Press, 2015)
Nonclinical Assessment of Abuse Potential for New Pharmaceuticals offers a complete reference on the current international regulatory guidelines and details best practice methodology for the three standard animal models used to evaluate abuse potential: physical dependence, self-administration and drug discrimination. This book also includes chapters on alternative models and examples of when you should use these alternatives. Case histories are provided at the end of the book to show how the data generated from the animal models play a pivitol role in the submission package for a new drug. B.